Implementation of 21st Century Learning Oriented to the Independent Curriculum in Islamic Religious Education Learning at SMA Negeri 1 Tarik Sidoarjo - Bayufirman, Bayu Firman; JalilulChakam, Achmad; Badriyah, Laila (Lembaga Penelitian dan Pendidikan Mandala, 2023)
Learning in the 21st century era faces various complex challenges. In the midst of this situation, the world of education has a crucial role and responsibility in facing and responding to these challenges. The government has taken innovative steps by introducing an independent curriculum as an effort to overcome these challenges. This research is qualitative research with a descriptive character. The data collection techniques used were in-depth interviews, observation and documentation. Data analysis is carried out through data reduction, data presentation and then drawing conclusions. The results showed that: 1. Learning at SMA Negeri 1 Tarik Sidoarjo applies the 4C principles (Critical thinking, creativity, collaboration, and communication), 2. The supporting factors for the 21st century learning process are adequate facilities and infrastructure, 80% of learning uses digital media, supported by teachers' IT mastery. Meanwhile, the inhibiting factor regarding the material which according to students and parents is a bit burdensome is because there are a few projects, a little work. As well as parents or guardians complaining about their children's return home being sometimes late or often having a lot of extra work.